Knowledge of dental surgeons on dental care in pregnant women (Research, Society and Development, 2021)
In the oral cavity, caries, gingivitis and periodontitis are commonly found in pregnant women and need to be treated. However, care with this audience requires a lot of attention, resulting from many doubts of dentists. Therefore, the objective of this study is to describe the assistance to pregnant women in dentistry, gathering protocols and assessing whether the knowledge of dentists is sufficient to provide safe care for pregnant women and their babies. For this, a narrative review of the literature was carried out that used as descriptors: pregnant women, dentistry and pediatric dentistry. Articles, monographs and dissertations were used in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS), BBO (Brazilian Bibliography of Dentistry), MEDLINE (National Library of Medicine) and Google Scholar, being selected the articles primarily by title and abstract and then, more specifically, meeting the inclusion and exclusion criteria. Through the review, it can be stated that pregnant women should have priority in dental care programs, and dental surgeons should seek to demystify myths and beliefs surrounding care. Most studies have shown that, although many professionals say they feel safe, this did not guarantee that some dentists would correctly answer some questions. Therefore, it is necessary that more and more these professionals become able to provide this service, either through the elaboration of protocols or that higher education institutions approach this content in a more intensive way, as the treatment for pregnant women should never be neglected.